Peran Politik Muhammadiyah Tahun 2010-2014 - Syahputra, Hikmawan (Jurnal Mahasiswa Ilmu Pemerintahan, 2014)
Muhammadiyah is the society organization that focuses on socio-religious area. Ascivil society, Muhammadiyah since birth has committed to contribute in building thenation and is shown through accelerating intelligence, religious enlightenment, andcommitment to humanity. As Alexis de Tocqueville described the concept of civil societythat the position of civil society has its own political power of the State as a countervailingforce. Muhammadiyah is not a political organization nor have organizational ties to anypolitical party, but Muhammadiyah has a strategic vision from birth to actively participatein politics, form and function development and empowerment, as well as the position itselfin the presence of state/government, Muhammadiyah always develops the attitude ofcommanding the good and forbidding the evil in the sense of providing support to positivepolicies, otherwise criticizes wisely to policies that are not well regarded. Entering secondcentury of its age, which starts from the 46th Congress in 2010 until late 2014 election,Muhammadiyah will continue to build the nation by increasing the role of nationality tothe community, state and nation. Carrying out the role of national commitment to runearly, the current age Muhammadiyah does such activities; First, increasing empowering,coaching, development and political education, second, increasing the involvement andparticipation of the actual nationality of the problems and issues of contemporarynationality, third, strengthen networks, communication and relationships betweenorganizations and government agencies, and the fourth, increasing the advocacy functionincluding action and service to the public interest.Keywords: Muhammadiyah, Civil Society, Role of Politics.